2016
DOI: 10.1111/jam.13076
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature, light and incubation period on production, germination and bioactivity ofTrichoderma atroviride

Abstract: Most studies on Trichoderma-based BCA have only shown the effect of culture conditions on the high conidia yield regardless of conidium quality. This study is the first report on conidium quality affected by principal culture conditions for Trichoderma biological control formulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
10
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 37 publications
6
10
0
3
Order By: Relevance
“…S1a,b). This suggests a bimodal population cycle, possibly resulting from a bimodal conidium production cycle similar to that described previously (Daryaei et al 2016b), but following a different time frame. Although depletion of nutrients can stimulate conidium production (Horwitz et al 1985;Betina 1995), ageing-induced conidiation initiated by gene regulation has been postulated as the main stimulation for conidium production rather than nutrient status (Chovanec et al 2001).…”
Section: °C-dextrosesupporting
confidence: 78%
See 3 more Smart Citations
“…S1a,b). This suggests a bimodal population cycle, possibly resulting from a bimodal conidium production cycle similar to that described previously (Daryaei et al 2016b), but following a different time frame. Although depletion of nutrients can stimulate conidium production (Horwitz et al 1985;Betina 1995), ageing-induced conidiation initiated by gene regulation has been postulated as the main stimulation for conidium production rather than nutrient status (Chovanec et al 2001).…”
Section: °C-dextrosesupporting
confidence: 78%
“…Similarly, previous studies have shown that T. atroviride LU132 outcompeted R. solani on dual plate assays (Daryaei et al . ,b,c,d,e). It has been suggested that Trichoderma metabolites contribute fungistatically to supress the growth and development of R. solani in soil or in agar dual cultures, which are proposed to be differentially modulated by NADPH oxidase (Dr Artemio Mendoza‐Mendoza 2014; personal communication).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Esse microrganismo atua no controle de diversos fitopatógenos por diferentes mecanismos de ação, como antibiose, micoparasitismo, produção de enzimas degradadoras da parede celular, competição por nutrientes e substrato e indução de resistência (Pereira et al, 2014). Também são caracterizados por serem resistentes a substancias tóxicas produzidos por outros microrganismos e tolerantes a diferentes tipos de fungicidas (Daryaei et al, 2016), o que os tornam de elevado interesse para uso como agente de controle biológico de fitopatógenos.…”
Section: Introductionunclassified